Observation of the B+c meson in Pb-Pb and pp collisions at √sNN=5.02 TeV and measurement of its nuclear modification factor - Tumasyan, Armen; Adam, Wolfgang; Andrejkovic, Janik Walter; Borshch, Vladislav; Ivanchenko, Vladimir; Tcherniaev, Evgueni (Physical Review Letters)
The B-c(+) meson is observed for the first time in heavy ion collisions. Data from the CMS detector are used to study the production of the B-c(+) meson in lead-lead (Pb-Pb) and proton-proton (pp) collisions at a center of-mass energy per nucleon pair of root s(NN) = 5.02 TeV, via the B-c(+) -> (J/psi -> mu(+)mu(-))mu(+)nu(mu) decay. The B-c(+) nuclear modification factor, derived from the Pb-Pb-to-pp ratio of production cross sections, is measured in two bins of the trimuon transverse momentum and of the Pb-Pb collision centrality. The B-c(+) meson is shown to be less suppressed than quarkonia and most of the open heavy-flavor mesons, suggesting that effects of the hot and dense nuclear matter created in heavy ion collisions contribute to its production. This measurement sets forth a promising new probe of the interplay of suppression and enhancement mechanisms in the production of heavy-flavor mesons in the quark-gluon plasma.